Examining the mediating role of job involvement in the relationship between job crafting and talent retention - Ahmad Nasser Abuzaid (Global Business & Finance Review (GBFR), 2024)
Purpose: In the current dynamic and intensely competitive global business landscape, the retention of highly skilled and specialized talent has emerged as a critical challenge. Employee retention is a strategic differentiator for organizational success, given the substantial expenses related to recruitment, the diminishment of know-how and expertise, and the often underestimated impact on performance. This study examined how job involvement acts as a mediator between the connection of job crafting and talent retention within the context of highly skilled employees in five-star hotels based in Jordan. Design/methodology/approach: A group of 419 participants successfully filled out the study survey. A quantitative cross-sectional survey design was adopted to test the research hypotheses, and the collected data were subjected to analysis using partial least squares through WarpPLS 8.0 software. Findings: The study's results offer statistical support for the positive influence of both crafting the job and job involvement on talent retention. Additionally, it was discovered that job crafting had been an indicator of increased job involvement. Moreover, the study reveals that the connection between job crafting and talent retention is mediated by job involvement. Research limitations/implications: The study findings carry significant implications for organizations. To effectively enhance talent retention, hotels should promote job crafting practices while fostering a work culture that nurtures job involvement. By embracing such approaches, hotels can form an environment where talented staff sense motivated, involved, and committed, contributing to the hotels' long-term goals achievement and competitive advantage. Originality/value: Recognizing the gaps in existing literature makes the need for further research evident. Scholars highlighted the need for or a greater abundance of empirical evidence pertaining to managing adept human resources. Similarly, scholars emphasized the researchers' criticism of the goodness of theoretical articles on managing talent, particularly the need for empirical research. These studies underscored the necessity of delving deeper into this subject matter and contributing to filling the gaps in the literature. Thus, this study makes a significant contribution to the talent retention field.
Keywords: 650; Job crafting; Talent retention; Job involvement; Five-star hotels; Jordan